2005
DOI: 10.1093/jnci/dji430
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Chest Radiograph for Lung Cancer Detection in the Randomized Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial

Abstract: In the baseline screen, nearly half the cancers were stage I. Whether this experience results in a reduction in lung cancer mortality is yet to be seen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
73
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 25 publications
5
73
0
4
Order By: Relevance
“…6). More importantly, CXR missed 20 (80%) of the 25 clinical stage I cancers, so that CXR screening was stopped.The baseline ELCAP CXR results are similar to those found in the Mayo Lung Project (MLP) [21] and to the recently reported baseline results of the Prostate, Lung, Colorectal, and Ovarian (PLCO) trial [22] (Fig. 6), which implies that the three cohorts had similar risk characteristics for lung cancer.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…6). More importantly, CXR missed 20 (80%) of the 25 clinical stage I cancers, so that CXR screening was stopped.The baseline ELCAP CXR results are similar to those found in the Mayo Lung Project (MLP) [21] and to the recently reported baseline results of the Prostate, Lung, Colorectal, and Ovarian (PLCO) trial [22] (Fig. 6), which implies that the three cohorts had similar risk characteristics for lung cancer.…”
supporting
confidence: 84%
“…For colon cancer screening, new tests (e.g., colonoscopy and/or virtual colonoscopy with CT) have essentially replaced sigmoidoscopy, and the latter is used in the ongoing PLCO trial, but the efficacy of these new tests has not been tested using a randomized screening trial design. For lung cancer, CT was already available when the CXR and sputum trials were started in the mid 1980s, but CXR is still being tested in the PLCO trial [22, 62], and these results will not be reported in next decade. For coronary artery calcification screening with CT, no randomized trial has ever been performed, although large national cohort studies have been started.…”
Section: Advantages Of the Elcap Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no significant difference in the incidence of cancer between the screening and control groups. [16] In the analysis made in the following years, both groups were compared in terms of mortality; however, but there was no significant difference between them. [17] In the Early Lung Cancer Action Project (ELCAP) that was performed by Henschke et al in the USA, 1.000 people aged more than 60 years who had a history of more than 10 pack years of smoking were included.…”
Section: Discussionmentioning
confidence: 99%
“…Current and former smokers were the major portion of the participants diagnosed with lung cancer. 16 After 13 years follow up, cumulative lung cancer incidence rate was 20.1 per 10.000 person-years in the intervention group and 19.2 per 10.000 person-years in the usual care group (RR: 1.05; 95% CI: 0.98-1.12). After total 13 years follow up period, 1.213 participants died from lung cancer in the intervention group and 1.230 in the usual care group.…”
mentioning
confidence: 94%